Fig 5 - - Ciara Judge (20161514) (2024)
Inferred mean infection count trajectories from EpiFusion using only case incidence (orange), only the phylogenetic tree (purple) and both data types combined (green) (columns) for the three scenarios tested (rows). The true number infected over time is represented by the black line. 95%, 80% and 66% highest posterior density intervals are represented by increasingly dark shaded regions. Times of step-changes are marked by the vertical dotted lines for the step-change in sampling and transmission scenarios: a 10-fold increase in case and genomic sequence sampling rates on day 35 for the ‘Sampling’ step-change scenario, and a 3-fold increase in transmission rate on day 100 for the ‘Transmission’ step-change scenario.